Integration of STEAM Approach in Chemistry Learning to Develop Higher Order Thinking Skills (HOTS): Literature Review - Muhammad Rifqi Zidan; Umi Nur Khamidah; Ifah Silfianah (Universitas Lampung, 2025)
The STEAM approach is regarded as highly relevant for fostering critical thinking skills while aligning with the characteristics of chemistry learning, which inherently demands the integration of concepts, experimentation, and real-life applications. Moreover, STEAM plays a strategic role in preparing essential 21st-century skills for students. This study aims to conduct a literature review on the integration of STEAM in chemistry education with a particular focus on the development of higher-order thinking skills (HOTS). The review was carried out using a literature study method guided by the PRISMA protocol and involved the analysis of 34 published articles within the period of 2018–2025. The findings indicate that higher-order thinking skills enhanced through the STEAM approach include critical thinking, creative thinking, decision-making, logical reasoning, reflection, metacognition, analysis, evaluation, creation, and problem-solving. The development of these skills can be facilitated either through the independent implementation of STEAM or through its integration with various innovative instructional models, such as Project-Based Learning (PjBL), Problem-Based Learning (PBL), Design Thinking, RADEC, Inquiry, Deep Learning, Gamification, and Blended Learning. Instructional tools that have been developed—such as Student Worksheets (LKPD), E-Worksheets (E-LKPD), and E-Modules—have been proven effective in supporting the enhancement of students’ HOTS.